Sanur Village Festival : The spirit of revival - Anak Agung Gde Marvy Khrisna Pranamartha (Bali Tourism Journal, 2017)
As a form of spirit to revive the economic stretch in Sanur after the First and second Bali Bombing Incidents, an event was established on 2006 known as Sanur Village Festival. Entering the year 2017, SVF activities always become one of tourism attractions for both local and foreign tourists. The festival consists of various contests and competitions, art and cultural attractions, music as well as different types of environmentally-friendly activities. SVF also fosters synergy among communities of citizens, governments and state-owned enterprises (BUMN) to encourage productivity of creative economy and stimulate creativity of young talents. Tourism Minister, Arief Yahya said the event is an example of tourism development with community-based and highly successful. According to him, this event could be imitated by other areas in developing tourism destinations with similar models.